Kesehatan Mental dalam Psikologi Islam: Antara Zakiah Daradjat dan Abu Zayd al-Balkhi - Budiman, Ahmad Teguh (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2025)
This article examines the concept of mental health from the perspective of Islamic Psychology by comparing the thoughts of two prominent figures, Zakiah Daradjat and Abu Zayd al-Balkhi. Zakiah Daradjat, a pioneer of modern Islamic psychology, emphasizes the integration of mental health, religion, and education, viewing spiritual balance as a key factor in fostering psychological well-being. Meanwhile, Abu Zayd al-Balkhi, a classical Muslim scholar, introduced a holistic approach to mental health encompassing both physical and psychological aspects, as outlined in his work “Mashalih al-Abdan wa al-Anfus”. This study aims to explore the similarities and differences in their perspectives and their relevance in addressing contemporary mental health challenges. By employing literature analysis, the article concludes that their approaches significantly contribute to building a comprehensive framework for Islamic psychology. The integration of traditional and modern perspectives offers relevant solutions for addressing mental health issues grounded in Islamic values. Keywords – Abu Zayd al-Balkhi, Islamic Psychology, Mental Health, Zakiah Daradjat.